Comparative Analysis of Network Development Local Area Network (LAN) Fiber Optical Cable with Unshielded Twisted Pair (UTP) Cat 6 Cable at SMK Negeri 2 Tasikmalaya - Ashari, Ami; Rubiani, Hani; Manova, Yovi (iora, 2024)
The LAN Network at SMK Negeri 2 Tasikmalaya previously used media UTP Cat5e network with poor performance due to bandwidth UTP Cat5e is only 200 Mb/s, therefore the school choose to replace it network media with fiber optics, with a bandwidth that can reach 1 Gb/s. On the other there is still UTP Cat6 with the same bandwidth of 1Gb/s at a cost installation is lower than fiber optic network installation. Data collection on performance is carried out using the Quality of Service (QoS) approach with the parameters measured, namely Delay, Jitter, Packet loss and Throughput using Wireshark software. Performance of fiber optic and UTP Cat6 networks at SMK Negeri 2 Tasikmalaya in categorize â€œGoodâ€ according to Telecommunications and Internet Protocol Hormonization Over Network (TIPHON) standards. Test results from optical fiber obtained a delay of 2.58 ms, jitter of 2.38 ms, packet loss of 0.254 and throughput of 805.92 Mbps. The test results of the UTP Cat6 cable were obtained delay of 5.59 ms, jitter of 5.21 ms, packet loss of 0.559 and throughput of 623.73 Mbps.